Investigation on low-speed pre-ignition from the quantification and identification of engine oil droplets release under ambient pressure conditions. (15th October 2020) - Tormos, Bernardo; Garcia-Oliver, Jose M; Bastidas, Sophia; Domínguez, Beatriz; Oliva, Fermin; Cárdenas, Dolores
Highlights: Engine oil viscosity does not have a determining effect on the oil droplets release. Oil droplets release to the combustion chamber increases with the engine speed. Working conditions of 2500 rpm and oil at 80 °C had the greatest amount of scrapped oil. Image processing methodology applied to identify regions prone to appearance of oil. Piston thrust and anti-thrust sides are critical regions for the appearance of oil. Abstract: One source of low-speed pre-ignition in turbocharged gasoline direct injection engines is the presence of oil droplets in the combustion chamber. In this study, oil droplets released due to the piston reciprocating motion, have been quantified as function of oil viscosity and engine speed, by means of a motored test rig under ambient pressure conditions. Oil droplets were collected using a sandwich-like support and absorbing paper. An image processing methodology was developed to identify critical regions of the piston prone to the appearance of oil. Results show that oil is scrapped by the piston rings and released to the combustion chamber in zones transverse to the piston pin, at speeds as low as 500 rpm. Oil viscosity does not have a determining effect on the oil amount reaching the combustion chamber, while engine speed greatly increases this phenomenon, with a critical point at 2500 rpm and oil temperature of 80 °C.